EFFECT OF FOLIAR SPRAYING WITH NANO-ZINC ON GROWTH AND PRODUCTIVITY SOME FABA BEAN VARIETIES - J. J. Kadhim; D. S. K. Altai; N. Z. M. Alsaedi; S. E. Seadh (مجلة الأنبار للعلوم الزراعية)
This fieldwork was conducted in the North of Babil Governorate, Iraq, to test the foliar fertilization influence with nano zinc on growth, yield, and its elements of some faba bean varieties during the 2022/2023 season. The field trial was designed using a split-plot and organized in haphazard complete blocks with triple replications. The study specifies the core plots with the kinds of field beans, i.e., Aquadlge (Turkish origin) V1, Aquaduice a longue cross (American origin) V2, Luz de otono (Spanish origin) V3 and Otono star (Holand origin) V4, and the sub-plots were specified with foliar fertilization with nano zinc (0, 150, and 200 mg L-1). The development of the investigated faba bean types, yield, and components varied significantly, with V3 (Luz de otono, Spanish origin) being the highest character. There was a significant spraying impact with nano zinc levels on growth, yield, and its elements, as the 200mg nano zinc L-1 had the maximum average for these characteristics, with a significant difference from the 150 mg nano zinc L-1 and control treatment. Foliar spraying V3 plants with 200 mg nano zinc L-1 two times is recommended at the first part of the flowering phase, and the second is at the 75% flowering phase in the ecological conditions of the research area.